Cerdas Finansial Atau Konsumtif? Hubungan Antara Literasi Keuangan dan Perilaku Konsumsi Siswa SMA - Sutina Sutina; Putri Restoening Muslimah; Toto Widiarto; Ari Wahyu Leksono; Rani Noviyanti (Universitas Galuh, 2026)
The growth of digital consumer culture has made financial literacy increasingly important for students’ everyday consumption decisions. This study examined the relationship between financial literacy and consumption behavior among 35 students from SMA PGRI 4 Jakarta using a quantitative correlational design and convenience sampling. Data were collected through a Likert-scale questionnaire and analyzed using descriptive statistics, a normality test, and Spearman’s rank-order correlation. The results showed a significant negative relationship between financial literacy and consumption behavior (rₛ = –0.462, p = 0.005), indicating that students with higher financial literacy tend to exhibit more rational and controlled consumption behavior. These findings emphasize the importance of strengthening financial literacy education to foster responsible consumption habits among students in the digital era.